An evaluation of product pricing, a case study of Mass beverages ltd. - Mangezi, Blessing (Midlands State University, 2017)
The research intended to evaluate the product pricing at Mass beverages ltd. Mass beverages Ltd 2013 annual report noted that the preference of prices charged by Schweppes Zimbabwe is insufficient to cover cost of producing the beverages as Schweppes continue decreasing the prices of its products. The research objective was to identify the product pricing policy and its determinants, detect the pricing implementation guidelines which are in place and suggest the best practice in product pricing at Mass beverages ltd. To accomplish the research the researcher used literature review from the various authors mostly text books to get insight of the product pricing policy and its determinants. The researcher used questionnaires and interviews to gather data concerning the product pricing policy at Mass beverages. The responses from Mass beverages management and employees evidently exposed that the product pricing policy charges prices which are insufficient to cover the cost of production which is leading to reduction of profitability. The researcher recommended that there is need for adjustments on the product pricing policy taking into account the cost of production thus considering best practices by other companies such as target costing and kaizen costing